Women Reading Popular Press: an Analysis of Merapi and Pos Kota readers - Puji Rianto (Department of Communications, Universitas Islam Indonesia, 2018)
This research examines how women read the popular press. The main question of this research is to what extent the popular press has relevance and functional values for women readers? The study was conducted on the readers of two popular newspapers in Indonesia, Merapi in Yogyakarta and Pos Kota in Jakarta. Through in-depth interviews, the study found that women have a pleasure of reading popular press because of its relevance and functionality. Although most of the news tells about crime and violence, those themes are relevant and functional for their daily life. The informants read almost all the criminal news. According to them, the criminal news provide information about what is happening in their environment so that they can always be careful, mainly related to the supervision of their children. In contrast, women do not particularly like political news because it is irrelevant to their life. In this case, political news is considered as male domain. The cultural factors also provide relevance for women readers, especially Merapi. The women who read Merapi very enjoy reading mystery stories, Jagad Lelembut, which is closely related to their local culture contexts.Keywords: popular press; women readers; Pos Kota; Merapi; relevance; functionality.